Genetic Association of Olanzapine Treatment Response in Han Chinese Schizophrenia Patients - Zhou, Wei; Xu, Yong; Lv, Qinyu; Sheng, Yong-hui; Chen, Luan; Li, Mo; Shen, Lu; Huai, Cong; Yi, Zhenghui; Cui, Donghong; Qin, Shengying (Frontiers in Pharmacology, 2019)
Olanzapine, a second-generation antipsychotic medication, plays a critical role in current treatment of schizophrenia (SCZ). It has been observed that the olanzapine responses in schizophrenia treatment are different across individuals. However, prediction of this individual-specific olanzapine response requires in-depth knowledge of biomarkers of drug response. Here, we performed an integrative investigation on 238 Han Chinese SCZ patients to identify predictive biomarkers that were associated with the efficacy of olanzapine treatment. This study applied HaloPlex technology to sequence 143 genes from 79 Han Chinese SCZ patients. Our result suggested that there were 12 single nucleotide polymorphisms (SNPs) had significant association with olanzapine response in Han Chinese SCZ patients. Using MassARRAY platform, we tested that if these 12 SNPs were also statistically significant in 159 other SCZ patients (independent cohort) and the combined 238 SCZ patients (composed of two tested cohorts). The result of this analysis showed that 2 SNPs were significantly associated with the olanzapine response in both independent cohorts (rs324026, P = 0.023; rs12610827, P = 0.043) and combined SCZ patient population (rs324026, adjust P = 0.014; rs12610827, adjust P = 0.012). Our study provides systematic analyses of genetic variants associated with olanzapine responses of Han Chinese SCZ patients. The discovery of these novel biomarkers of olanzapine-response will facilitate to advance future olanzapine treatment specific for Han Chinese SCZ patients.